2015
DOI: 10.1121/1.4929692
|View full text |Cite
|
Sign up to set email alerts
|

On the use of evanescent plane waves for low-frequency energy transmission across material interfaces

Abstract: The transmission of airborne sound into high-impedance media is of interest in several applications. For example, sonic booms in the atmosphere may impact marine life when incident on the ocean surface, or affect the integrity of existing structures when incident on the ground. Transmission across high impedance-difference interfaces is generally limited by reflection and refraction at the surface, and by the critical angle criterion. However, spatially decaying incident waves, i.e., inhomogeneous or evanescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Two main types of air-to-ground conversion coexist: classical acoustic wave to seismic wave transmission (Aki & Richards, 2002) and compliance effects (Kenda et al, 2017;Sorrells, 1971;Sorrells et al, 1971). A smooth transition links the two (Woods et al, 2015). Additionally, studying the ground displacements caused by infrasonic waves enables one to constrain the subsurface below the InSight lander.…”
Section: Introductionmentioning
confidence: 99%
“…Two main types of air-to-ground conversion coexist: classical acoustic wave to seismic wave transmission (Aki & Richards, 2002) and compliance effects (Kenda et al, 2017;Sorrells, 1971;Sorrells et al, 1971). A smooth transition links the two (Woods et al, 2015). Additionally, studying the ground displacements caused by infrasonic waves enables one to constrain the subsurface below the InSight lander.…”
Section: Introductionmentioning
confidence: 99%
“…This work extends that of Vanaverbeke et al, 22 who demonstrated that bounded inhomogeneous waves improve the surface wave excitation efficiency as compared to Gaussian and square waves, by examining the effect of tuning the decay parameter. It was shown here that the minimum in the plane wave reflection coefficient with respect to the decay parameter 23,24 provides a good prediction of the minimum in the local reflection coefficient for bounded wave profiles, which is exact in the limit of large beamwidths. Inhomogeneous plane wave theory also provides an indication of the decay parameter value which maximizes the surface wave excitation efficiency, but this value is sensitive to the beamwidth of bounded waves and there is generally a shift to larger decay parameter values due to the greater spatial concentration of the incident wave energy at those larger decay rates.…”
Section: Discussionmentioning
confidence: 78%
“…For the plane wave, the decay parameter gives the rate of exponential decay perpendicular to the propagation direction. 23,30,31 As is evident, the form of the plane wave reflection coefficient, including the location of the minimum, is closely matched by the local reflection coefficients for the wider beamwidths. The decay parameter which yields the minimum for the profile with the half beamwidth W ¼ 30 mm is b ¼ 110:8 rad/m, which gives a 0:18% error with respect to the value for the plane incident wave, b ¼ 111:0 rad/m.…”
Section: A Water-stainless Steel Interfacementioning
confidence: 68%
See 2 more Smart Citations